The Influence of Shipping Costs and Returns on Consumer Purchase Decisions in Patumbak Village Deli Serdang District Village - Mariyati Harahap; Toni Hidayat (International Journal of Economics (IJEC), 2022)
This research is entitled "The Effect of Shipping and Return on Purchase Decisions of Shopee Consumers in Patumbak Village, Deli Serdang Regency". The purpose of this study was to determine whether there is an effect of postage and return on the purchasing decisions of shopee consumers in Patumbak Village, Deli Serdang Regency. The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 1,652 (for 6 months) shopee consumers in Patumbak Village, Deli Serdang Regency ", using random sampling as many as 95 respondents. The method used in this research is descriptive quantitative method. The data analysis technique used multiple linear regression analysis with the regression equation Y = 3.198 + 0.116X1 + 0.919X2 + e. Partial test results (t) are obtained at 727 for postage and 7346 for Returns. While the results of the simultaneous F-Test obtained were 93,669. And the results obtained in this study indicate an R2 value of 81.9%, so it can be concluded that Shipping and Return Costs to Shopee Consumer Purchase Decisions in Patumbak Village, Deli Serdang Regency and the remaining 32.9% are influenced by other factors, price, product discounts. and product accessories.